Development of Augmented Reality-Based Interactive Learning Media on Swimming Material for Physical Education Learning - Latuheru, Ricardo Valentino (Journal of Sport Education, Coaching, and Health (JOCCA), 2025)
This study aims to develop and evaluate the effectiveness of interactive Augmented Reality (AR)-based learning media for swimming for seventh-grade students at SMP Negeri 24 Makassar. The research background stems from the low understanding of swimming techniques in schools without swimming pool facilities, as well as the need for innovative learning media that can bridge theory and practice. The research method used a Research and Development (R&D) approach, adapting the Borg & Gall model, involving 40 students as a sample. The research instruments included cognitive tests, psychomotor observation sheets, motivation questionnaires, and questionnaires assessing media effectiveness. The results showed a significant increase in students’ cognitive understanding, with an average pretest score of 56.25 increasing to 82.75 in the posttest. A paired t-test showed a p-value <0.05, indicating the effectiveness of AR in improving understanding of basic swimming techniques. Improved psychomotor skills were also evident in the average score, which increased from 1.96 to 3.44, particularly in aspects of body position and motor coordination. Student learning motivation increased with a score of 3.57, and student perception of media effectiveness reached 3.71. Overall, AR media has proven effective in improving students’ understanding of swimming techniques, learning motivation, and motor readiness. AR is recommended as an innovative learning solution, especially for schools with limited swimming facilities. Further research is recommended to test the effectiveness of AR in real-life swimming practice in a pool.